Financial Performance Assessment Analysis Using Economic Value Added (EVA) Method - Musyafa’ Musyafa’; Khulaimah Sakdiyah (NUsantara Islamic Economic Journal, 2022)
This study masterless to determine the financial performance with the method of economic value added (EVA) at Bank Muamalat Indonesia Tbk. Data processing using Microsoft Office Excel. The analysis method used in this research is qualitative descriptive analysis, where the data used are secondary data obtained from the financial statements of PT Bank Muamalat Indonesia Tbk for the period 2016-2019 with the documentation data method. The results of the financial statement data of Bank Muamalat Indonesia Tbk from 2016 to 2019 show that the financial performance of the Bank using the EVA method produces a negative EVA value. The bank has not been able to provide benefits for investors, both creditors and shareholders.